Vannamei Shrimp Agribusiness Sustainability in Parigi Moutong Regency - Haris Ali Maulana (Athallah Publishing globalindo, 2025)
This research generally aims to determine and analyze the sustainable vaname shrimp agribusiness development model. Whereas specifically aims to examine the sustainability status of vaname shrimp agribusiness in Parigi Moutong Regency. The sustainability status will be analyzed using Rapfish with five dimensions developed at the research location which are based on considerations that can reflect existing conditions . The results of the research show that the sustainability of the use of vaname shrimp fishery resources in Parigi Moutong Regency from the five dimensions is shown in the kite diagram which overall is at an index value of > 50% indicating that The sustainability status of vaname shrimp agribusiness in Parigi Moutong Regency is good and quite sustainable . The government's efforts in overcoming problems in the sustainable management of vaname shrimp resources by cultivators and other stakeholders must be carried out in an integrated and well-coordinated manner by the Parigi Moutong Regency government with interested parties.